Tecnologías de la información y comunicación y su contribución en el desempeño profesional de los docentes de la escuela de Educación Básica “Babahoyo” del cantón Babahoyo, Provincia de los Rios - Ortega López, Luis Eugenio (2017)
and communication technologies are increasingly being used by teachers. Although presented as one of the tools from which much updated information can be obtained, there is also the possibility of producing and transforming environments of relationship in education. These powerful tools in the professional performance facilitate the management and attention of the students towards the teachers, since it manages to incorporate multiple multimedia strategies, producing a resource in which text, images, audio and video are integrated for the teaching processes. The current final report is intended to make a study of the professional performance of information and communication tools in teachers and to assess the need to plate a manual to improve the skills in this use for Babahoyo Elementary School This will be done a theoretical framework on the main characteristics of a manual, its elements, mention the basic knowledge to be had and additional multimedia tools. The research was framed in the methodology of chi square, which allowed to test the hypothesis Which was raised.